Pengaruh Islamicity Performance Index Terkait Nilai Perusahaan dengan Konsep Maqashid As-Syariah - illah, Muhamad Atho’; Sundari, Sri; Boedoyo, M. Sidik; Sianipar, Leo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Islamicity Performance Index is a performance measurement tool that is able to reveal the materialistic and spiritual values ​​that exist in sharia companies. Performance measurement using the Islamicity Performance Index is only based on information available in the annual financial reports. This index refers to Profit Sharing Ratio, Zakat Performance Ratio, Equitable Ratio, Director Employess Welfare Ratio, Islamic investment vs non-Islamic investment, Islamic income vs non-Islamic income and AAOFI index. The results of this study indicate that Islamic financial performance (Islamicity Performance Index) is able to significantly and positively influence company value as measured using the concept of Maqashid as-Syariah. So that if the Islamic financial performance (Islamicity Performance Index) in the ranking is considered UNSATISFACTORY, it will have an impact on company value in the Maqashid as-Syariah concept which also tends to get a bad rating in the eyes of investors. And vice versa, if the rating is considered SATISFACTORY, then the value of the company will tend to get a good assessment and added value in the eyes of investors. Firm size is able to negatively moderate (weaken) the relationship of the Islamicity Performance Index to firm value in Islamic Commercial Bank companies. The results that occurred in this study could also be caused by macroeconomic factors that greatly affect the performance of Islamic banking in Indonesia with an increase in inflation which has a negative impact on Islamic banking financial performance (ROA). Keywords: Islamicity Performance Index; syariah companies; Maqashid as-Syariah